ADMM‐Based Distributed Algorithm for Energy Management in Multi‐Microgrid System - Lou, Huen; Fujimura, Shigeru (IEEJ Transactions on Electrical and Electronic Engineering, 2024)
This article focuses on Energy Management Problem (EMP) in Muti‐microgrid systems. Each microgrid (MG) has four basic equipments including Renewable Generator (RG), Fuel Generator (FG), Storage Device (SD) and Smart Load (SL). In consideration of equipment capacity, confidence interval for forecasts of RG output, supply–demand balance and other factors, an optimization model with the objective of minimizing operation cost was established. Through Lagrange dual problem and variable substitution, we transform the centralized problem into an equivalent distributed form. Then, a completely distributed algorithm based on Alternating Direction Method of Multipliers (ADMM) and Average Consensus (AC) is proposed to attain a global optimal schedule plan. The algorithm overcomes the defect that each microgrid needs to know the total must‐run load in advance. At the same time, the electricity clearing price is related to the objective function through Lagrange dual variables, which can be obtained while the optimal plan is determined. Finally, the simulation verifies the convergence of the algorithm, and the calculated optimal cost is the same as that of the centralized method, ensuring its effectiveness. Besides, the algorithm also has good performance in plug‐and‐play scenarios. © 2023 Institute of Electrical Engineer of Japan and Wiley Periodicals LLC.